Investigation of baffle configuration effect on the performance of exhaust mufflers - Ahmed Elsayed; Christophe Bastien; Steve Jones; Jesper Christensen; Humberto Medina; Hassan Kassem (Case Studies in Thermal Engineering, 2017)
Using baffles in exhaust mufflers is known to improve their transmission loss. The baffle cut ratio should affect the muffler performance analogous to a shell-and-tube heat exchanger. To the authors’ knowledge, there is no previous assessment reported in literature of the effects that the baffle cut ratio configuration has on acoustic response and back pressure. This investigation presents a parametric study on the effect of baffle configuration on transmission loss and pressure drop predicted. The effect of (i) the baffle cut ratio and baffle spacing, (ii) the number of baffle holes, and (iii) the hole distribution for their effect on transmission loss was investigated. Results show that decreasing the baffle cut ratio tends to increase the transmission loss at intermediate frequencies by up to 45%. Decreasing the spacing between muffler plates was shown to enhance the muffler transmission loss by 40%. To assess the baffle effect on flow, the OpenFoam CFD libraries were utilized using the thermal baffle approach model. Baffles were found to cause sudden drop in fluid temperature in axial flow direction. The outlet exhaust gases temperature was found to decrease by 15% as the baffle cut ratio changed from 75% to 25%.